City-states in relational urbanization: the case of Luxembourg and Singapore. Issue 4 (21st April 2022) - Wong, Catherine; Hesse, Markus; Sigler, Thomas J.
ABSTRACT: Post-industrial global urbanization has seen the rise of territorial economic development strategies predicated on reconfiguring the urban landscape to conform to novel forms of economic production, often under the guise of "global city" development. This paper reorients the conversation on global city development by highlighting the intermediary roles that particular cities play in brokering flows of global knowledge, goods, and capital through novel spatial-economic configurations. We identify a sub-set of city-states characterized by territorial economic development strategies that are exemplary of "relational" processes. Luxembourg and Singapore serve as illustrative cases in which urban territorial development is guided almost entirely by an exogenous orientation benefitting from an intermediary positionality. Although all cities are in some way "relational" in their politico-economic orientation, these extraordinary cases highlight a number of novel concurrent socio-spatial processes which enabled them to capture key advantages conferred by their positionality in relation to regional and global flows.